1980
DOI: 10.1139/z80-065
|View full text |Cite
|
Sign up to set email alerts
|

Scent marking in coyotes

Abstract: The scent marking behaviour of coyotes, Canis latrans, was studied in Jasper National Park, Alberta, during the period 1974–1976. Results show that adult males and females scent mark throughout their territory at all times of the year. Urine is most frequently used in marking. The rate of scent marking at the edge of the territory is approximately twice that in the center. This increase is accomplished by reducing the distance between scent-mark sites and increasing the proportion of multiple marks. All member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
59
2
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 0 publications
13
59
2
1
Order By: Relevance
“…Previous studies have suggested that coyotes may be more attentive along the periphery or outside their home areas (Hibler 1977;Bowen and Cowan 1980). Scent station survey lines on roads that coyotes treat as territorial boundaries may elicit more visits than those passing through the middle of territories.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have suggested that coyotes may be more attentive along the periphery or outside their home areas (Hibler 1977;Bowen and Cowan 1980). Scent station survey lines on roads that coyotes treat as territorial boundaries may elicit more visits than those passing through the middle of territories.…”
Section: Discussionmentioning
confidence: 98%
“…The higher proportion of roads acting as home-range boundaries and the behaviors associated with such boundaries, i.e., scent-marking and increased attentiveness (Camenzind 1978;Bowen and Cowan 1980;Wells and Bekoff 1981;Gese and Ruff 1997), may have resulted in greater scent station visitation rates along these roads. We are not implying that coyotes do not thoroughly explore the core areas of their home ranges, but as familiarity with a particular environment increases, habituation may replace attentiveness and exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to wolves, all adult coyotes urine-mark, females as well as males (Barrette and Messier, 1980;Bowen and Cowan, 1980;Wells and Bekoff, 1981). Furthermore, although there are seasonal peaks, females as well as males urine-mark year-round (Wells and Bekoff, 1981).…”
Section: Role Of Social Rankmentioning
confidence: 95%
“…Howling and scent-marking are indirect means of territory defense and maintenance and have been documented for wolves (Peters and Mech 1975;Rothman and Mech 1979;Harrington and Mech 1978a, 1978b, 1983Harrington 1987) and coyotes (Camenzind 1978;Barrette and Messier 1980;Bowen and Cowan 1980;Gese andRuff 1997, 1998). Observations of direct territory defense are more difficult to acquire, owing to the secretive nature of wild canids.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and Orians (1970) proposed that territoriality is implied if there is little overlap between home ranges, scent-marking behavior is performed, and agonistic interactions occur. Several studies have demonstrated direct and indirect mechanisms that many carnivore species use to maintain their territory boundaries, including scent-marking (Peters and Mech 1975;Camenzind 1978;Rothman and Mech 1979;Barrette and Messier 1980;Bowen and Cowan 1980;Wells and Bekoff 1981;Bailey 1993;Caro 1994;, howling (Harrington and Mech 1978a, 1978bGese and Ruff 1998), and confronting intruders (Camenzind 1978;Bekoff and Wells 1986;Mech 1993Mech , 1994.…”
Section: Introductionmentioning
confidence: 99%